2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683655
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Time-Scale Generalized Fair Scheduling for Amplify-and-Forward Relay Networks

Abstract: Abstract-We devise an optimization framework for generalized proportional fairness (GPF) under different time scales for amplify-and-forward (AF) relay networks. In GPF scheduling, a single input parameter is used to change the fairness from throughput optimal, to proportionally fair and asymptotically to max-min fair. We extend the GPF scheduling to include a new input parameter, which determines the time-scale of fairness from short-term GPF to long-term GPF. We devise a low-complexity near-optimal algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This feature gives the opportunity to adapt the transmission across sub-channels, among WTs, and dynamically between frames [14]. To exploit this feature in packet scheduling, RB allocation, and AMC control, we select the OFDMA as the access technology in our study.…”
Section: Ofdmamentioning
confidence: 99%
See 2 more Smart Citations
“…This feature gives the opportunity to adapt the transmission across sub-channels, among WTs, and dynamically between frames [14]. To exploit this feature in packet scheduling, RB allocation, and AMC control, we select the OFDMA as the access technology in our study.…”
Section: Ofdmamentioning
confidence: 99%
“…For asymptotic optimality proof of gradient algorithm see [18,50]. Using the previous observation about the objective function, we devised an iterative greedy heuristic algorithm for amplify-and-forward (AF) relay context in [14,20,21]. It has been reported that the Taylor approximation works closer to optimal when NT /|Φ| >> 1, especially for short-term fairness.…”
Section: Optimalitymentioning
confidence: 99%
See 1 more Smart Citation